Utilizing Environmental DNA to Identify Eukaryotic Diversity in Mangrove Sediments at Demak, Central Java, Indonesia - Cahyani, Ni Kadek Dita; Jumari, Jumari; Hariyati, Riche; Rahadian, Rully; Rahim, Aulia; Zega, Enita Setiawati; Kholifah, Rizqi Widya Nur; Barber, Paul Hendry; Putro, Sapto Purnomo; Soeprobowati, Tri Retnaningsih (Marine Science Department Diponegoro University, 2024)
The mangrove ecosystem, found along tropical and subtropical coasts, adapts to extreme conditions like rapid tidal changes, high salinity, anthropogenic influences, and anoxic environments. Mangrove sediments host diverse organisms, particularly invertebrates and bacteria, which significantly influence sediment structure and biochemical processes by enhancing permeability and water flow. Modern molecular approaches, notably Next-Generation Sequencing (NGS), are increasingly used to identify macro and microorganism communities in sediments. NGS, a powerful tool for DNA and RNA sequencing, allows for parallel sequencing of numerous DNA fragments, providing comprehensive insights into genome structure, genetic variants, gene expression, and epigenetic modifications. Its efficiency and cost-effectiveness make NGS vital for both basic biological research and clinical diagnostics. Recent NGS studies on mangrove sediments have focused on bacterial, archaeal, and fungal diversity. The study examines eukaryotic diversity in mangrove sediments at two locations, targeting the Cytochrome Oxidase Subunit I (COI) gene, a universal marker for eukaryotes. Results indicate distinct taxa at each site with minimal overlap, demonstrating eDNA's potential for assessing both macro and microorganism diversity in mangrove sediments. This preliminary study underscores the utility of molecular techniques in biodiversity research and also dynamic ecosystem changes in the mangrove sediment ecosystem. The high influence of the environment around the mangrove ecosystem will affect the quality of the mangrove itself. eDNA here provides a fast method for recording possible changes to be able to carry out better management in the future.